Zetta Theodoropoulou Polychroniadis and Doniert Evely (eds). AEGIS. Essays in Mediterranean archaeology presented to Matti Egon by the scholars of The Greek Archaeological Committee - Dickinson, Oliver (Journal of Greek Archaeology, 2016)
As its title makes clear, this is a collection of 23 papers presented as a festschrift to Matti Egon, the founder of The Greek Archaeological Committee UK, by a selection of past holders of scholarships granted by the Committee (some were unable to contribute for lack of time available). As such, it offers a good idea of the laudably wide range of topics that the Committee has been willing to support but, inevitably, it has no common theme. Although the majority of papers are concerned in some way with the Greek world, five lack any substantial ‘Hellenic’ link, two relating to Cyprus, one to Troy, one to the Phoenicians of southern Spain, and one to Mount Sinai.